Mean Polyp per Patient Is an Accurate and Readily Obtainable Surrogate for Adenoma Detection Rate: Results from an Opportunistic Screening Colonoscopy Program - Delavari, Alireza (Middle East J Dig Dis, 2015)
BACKGROUND The incidence of colorectal cancer is rising in several developing countries. In the absence of integrated endoscopy and pathology databases, adenoma detection rate (ADR), as a validated quality indicator of screening colonoscopy, is generally difficult to obtain in practice. We aimed to measure the correlation of polyp-related indicators with ADR in order to identify the most accurate surrogate(s) of ADR in routine practice. METHODS We retrospectively reviewed the endoscopic and histopathological findings of patients who underwent colonoscopy at a tertiary gastrointestinal clinic. The overall ADR and advanced-ADR were calculated using patient-level data. The Pearson’s correlation coefficient (r) was applied to measure the strength of the correlation between the quality metrics obtained by endoscopists. RESULTS A total of 713 asymptomatic adults aged 50 and older who underwent their first-time screening colonoscopy were included in this study. The ADR and advanced-ADR were 33.00% (95% CI: 29.52-36.54) and 13.18% (95% CI: 10.79-15.90), respectively. We observed good correlations between polyp detection rate (PDR) and ADR (r=0.93), and mean number of polyp per patient (MPP) and ADR (r=0.88) throughout the colon. There was a positive, yet insignificant correlation between advanced ADRs and non-advanced ADRs (r=0.42, p=0.35). CONCLUSION MPP is strongly correlated with ADR, and can be considered as a reliable and readily obtainable proxy for ADR in opportunistic screening colonoscopy programs.